PENGARUH STORY TELLING TENTANG KESIAPAN MENGHADAPI BENCANA GEMPA BUMI TERHADAP SELF EFFICACY ANAK PRASEKOLAH - Ririnisahawaitun, Ririnisahawaitun; Yuliyanti, Sasteri; Farlina, Baiq Fina; Junardi, Hariawan (Coping: Community of Publishing in Nursing, 2022)
The located in the Pasific ring of fire, Indonesia has high potential for disaster, such as earthquakes. Children are a vulnerable group to be victim. Self efficacy is needed to make  children have ability to act when disaster occurs. One of the effort to improve children’s self efficacy is by story telling. The aim of this study is to determine the effect of story telling about earthquake preparedness toward self efficacy of preschool. This study was a pre-experimental study, with a one pretest-posttest group design. The population of this study was all children in Childhood School at Tulus Ikhlas Al Habibi, Batuyang Village, Pringgabaya, East Lombok of 60 children was taken by total sampling. Collecting data using a self efficacy questionnaire was validity and reliability test. The intervention in this study was story telling using hand puppet media. Wilcoxon test showed there were the effect of story telling about earthquake preparedness toward children’s self efficacy (p value = 0,000).